Alterations in white matter micro-integrity of the superior longitudinal fasciculus and anterior thalamic radiation of young adult patients with depression. Issue 13 (6th March 2014) - Lai, C.-H.; Wu, Y.-T.
Abstract : Background: This study surveyed the characteristics of white matter (WM) micro-integrity in patients who were diagnosed with major depressive disorder (MDD) without co-morbidities. Method: A total of 44 patients with MDD and 27 normal controls were enrolled in our study. Diffusion tensor imaging images of patients and controls were pre-processed and analysed to estimate differences in WM micro-integrity between patients and controls by performing comparisons of the values obtained from fractional anisotropy (FA). FA outputs of patients and controls were compared by a non-parametric permutation-based method with global brain volume, age and gender as covariates. In addition, the between-group differences of radial diffusivity (RD) and axial diffusivity (AD) were assessed to explain the alterations in FA values. Correlations between clinical variables (such as depression severity, anxiety severity, illness duration) and FA values were also estimated in each group and across both groups. Results: The patients with MDD had significantly lower FA values than the controls, for the left superior longitudinal fasciculus (SLF) and the right anterior thalamic radiation (ATR). The reductions in FA values occurred in combination with elevated RD values in the bilateral SLF and decreased AD values in the bilateral ATR. FA values were negatively correlated with depression severity in the SLF and with illness duration in the right SLF and ATR. Conclusions: MDD patients had significant alterations in the WM micro-integrity of the left SLF and the right ATR.